2007
DOI: 10.1159/000103565
|View full text |Cite
|
Sign up to set email alerts
|

Development of Food-Based Dietary Guidelines for Iran: A Preliminary Report

Abstract: Iran is undergoing an epidemiological and nutritional transition. Over the last 2–3 decades, major changes in lifestyle and food consumption patterns have occurred, as well as in the socio-economic situation. Disease patterns have changed and some micronutrient deficiencies and chronic nutritional diseases, including obesity, are on the increase. Considering these, food habits, and the national food system, the Nutrition Department, Ministry of Health and Medical Education and the Iranian Nutrition Society joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…The corresponding intake of refined grains was 9?5 % in the US National Health and Nutrition Examination Survey (NHANES) 2001-2002 (35) . The fact that rice was the highest contributor to cereal intake in the present study, while it contributed only 5?3 % in NHANES (34) , confirms the results of previous research documenting rice as the staple food in the Middle East region (3,13) . On the other hand, the contribution of dark green vegetables to total vegetable intake in Tehranian adults was almost 30 %, a figure that is much higher than the recommended amount of 17 % (12) , while dark green vegetable intake accounted for less than 6 % of total vegetable intake in NHANES (35) .…”
Section: Discussionsupporting
confidence: 91%
“…The corresponding intake of refined grains was 9?5 % in the US National Health and Nutrition Examination Survey (NHANES) 2001-2002 (35) . The fact that rice was the highest contributor to cereal intake in the present study, while it contributed only 5?3 % in NHANES (34) , confirms the results of previous research documenting rice as the staple food in the Middle East region (3,13) . On the other hand, the contribution of dark green vegetables to total vegetable intake in Tehranian adults was almost 30 %, a figure that is much higher than the recommended amount of 17 % (12) , while dark green vegetable intake accounted for less than 6 % of total vegetable intake in NHANES (35) .…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore not surprising that dietary guidelines recommend that people consume plenty of F&V, including a variety of types and colours (National Health and Medical Research Council, 2013;Safavi et al, 2007; U.S. Department of Agriculture & U.S. Department of Health & Human Services, 2010). Although the benefits of eating F&V have been identified, most young people do not meet current guidelines for F&V intake.…”
mentioning
confidence: 99%
“…A study on dietary intakes could help nutritionist determine food patterns and their effect on some problems such as PMS symptoms in women. The Iranian food pyramid is an ap-propriate dietary pattern that was designed for Iranian adults (17) and by following the food pyramid guidance helps to improve overall health (18). No studies were found about the relationship between dietary patterns (according to food pyramid) and PMS emotional and physiological symptoms in Iranian women.…”
Section: Introductionmentioning
confidence: 99%